Micro‐CT Analysis of Rodent Temporal Bones: Identifying Optimal Species for Otological Research - Hannah Daoudi; Evelyne Ferrary; Cerine Moula; Florence Agnely; Amélie Bochot; Catherine Cailleau; Yann Nguyen; Ghizlène Lahlou; Renato Torres (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objectives Rodents are used in most otological research studies and the choice of the most appropriate animal model may be crucial in studies of ear diseases and in the development of effective treatments. Here, we used micro‐CT to compare temporal bone anatomy between four rodent model animals (guinea pigs, gerbils, rats, and mice) and humans, aiming to better characterize the anatomy of the inner and middle ear, and facial nerve to support informed animal model selection in otologic research. Methods We generated three‐dimensional reconstructions and measured the various middle (tympanic membrane, ossicular chain, and facial nerve) and inner (cochlea, vestibular labyrinth) ear structures. Results Each structure of the middle or inner ear of each rodent was described and measured. Conclusion This micro‐CT analysis of rodents can guide researchers in their choice of the most suitable middle or inner ear models based on the specific anatomic area of interest. Our findings highlight the strengths and limitations of each species, providing essential insight that could enhance the precision and applicability of otological studies. Level of Evidence 4.